AN ANALYSIS OF LANGUAGE STYLE PRESENTING MORAL VALUES FOUND IN RAINBOW TROOPS NOVEL - Teovila Edwin; Ida Bagus Gde Nova Winarta; Ni Nyoman Deni Ariyaningsih (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2022)
This study is primarily concerned style of presenting moral values in the Rainbow Troops by Andrea Hirata. This novel tells about how ten children struggle for their study and do many amazing experiences. The problems of the study focused on the style of presenting moral values and types of moral values in Rainbow Troops. This type of research is qualitative research. Method of collecting the data the method used in this research is the listening method and is combined with the note technique. The first step of this research is to collect conversation between character in the novel and the classify each use of style found language. Based on the result of the classification, the research analyses conversations containing figurative language and analyse meaning stylistic pragmatics. There are several sentences in this study, the language as follows allegorical language style, language style hyperbole, metaphorical language style, metonymy style, style simile and personification style.